“The particulars of loss”: Grief Memoirs and Their Pragmatic Applications - Katarzyna A. Małecka (Text Matters)
Death is commonly pushed to the periphery in contemporary society, leaving the grief-struck to endure the turbulent nature of their loss alone. Unsurprisingly, our mortality-denying times have witnessed the proliferation and popularity of grief memoirs. However, not every text will resonate with every reader, and the selection of appropriate, relatable texts is made more difficult with the overabundance of digital data in our lives. This essay explores select life-altering states of grief addressed in autobiographical accounts of loss and compares the details with the assessment of these states in bereavement literature. The correlations and disparities between the literary and the clinical reveal that the personal nature of grief memoirs makes them a suitable aid in the education of helping professionals and in therapy. Greater familiarity with grief memoirs among therapists may increase their visibility among the bereaved. To facilitate the selection and assessment of proper texts, a closer collaboration between literary scholars specializing in trauma narratives and helping professionals who use bibliotherapy is needed.